Principles of Biostatistics with CD - Marcello Pagano; Kimberlee Gauvreau (Cengage Learning, 2000)
Marcello Pagano and Kimberlee Gauvreau\\\'s PRINCIPLES OF BIOSTATISTICS, Second Edition is a concepts-based introduction to statistical procedures that prepares public health, medical, and life sciences students to conduct and evaluate research. With an engaging writing style and helpful graphics, the emphasis is on concepts over formulas or rote memorization. Throughout the book, the authors use practical, interesting examples with real data to bring the material to life.
Keywords: Biometry . Biostatistics